Influence of reduced muscle mass and quality on ventilator weaning and complications during intensive care unit stay in COVID-19 patients. Issue 12 (December 2022) - Damanti, Sarah; Cristel, Giulia; Ramirez, Giuseppe Alvise; Bozzolo, Enrica Paola; Da Prat, Valentina; Gobbi, Agnese; Centurioni, Clarissa; Di Gaeta, Ettore; Del Prete, Andrea; Calabrò, Maria Grazia; Calvi, Maria Rosa; Borghi, Giovanni; et al.
Summary: Background & aims: Sarcopenia, a loss of muscle mass, quality and function, which is particularly evident in respiratory muscles, has been associated with many clinical adverse outcomes. In this study, we aimed at evaluating the role of reduced muscle mass and quality in predicting ventilation weaning, complications, length of intensive care unit (ICU) and of hospital stay and mortality in patients admitted to ICU for SARS-CoV-2-related pneumonia. Methods: This was an observational study based on a review of medical records of all adult patients admitted to the ICU of a tertiary hospital in Milan and intubated for SARS-CoV-2-related pneumonia during the first wave of the COVID-19 pandemic. Muscle mass and quality measurement were retrieved from routine thoracic CT scans, when sections passing through the first, second or third lumbar vertebra were available. Results: A total of 81 patients were enrolled. Muscle mass was associated with successful extubation (OR 1.02, 95% C.I. 1.00–1.03, p = 0.017), shorter ICU stay (OR 0.97, 95% C.I. 0.95–0.99, p = 0.03) and decreased hospital mortality (HR 0.98, 95% C.I. 0.96–0.99, p = 0.02). Muscle density was associated with successful extubation (OR 1.07, 95% C.I. 1.01–1.14; p = 0.02) and had an inverse association with the number of complications in ICU (Β −0.07, 95% C.I. −0.13 - −0.002, p = 0.03), length of hospitalization (Β −1.36, 95% C.I. −2.21 - −0.51, p = 0.002) and in-hospital mortality (HR 0.88, 95% C.I. 0.78–0.99, p = 0.046). Conclusions: Leveraging routine CT imaging to measure muscle mass and quality might constitute a simple, inexpensive and powerful tool to predict survival and disease course in patients with COVID-19. Preserving muscle mass during hospitalisation might have an adjuvant role in facilitating remission from COVID-19. Highlights: Routine CT scans are useful to characterise muscle mass, density and quality. Preserved muscle mass and density predicted successful extubation in patients with SARS-CoV-2-related pneumonia. Low muscle mass and density predicted a fatal and/or complicated COVID-19 course.